Potential Fraud on Online Auction Business Via Instagram: Overview of Islamic Law and Indonesian Statutory Law - Nur Rizqi Febriandika; Jajang Nurzaman; Muhammad Reynaldi Ariananda Arkiang (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
This study aims to discuss the potential problem of auction fraud carried out by the @xxx Instagram account in terms of Islamic law and Indonesian law. The research method used is descriptive qualitative, through a normative juridical approach, and is complemented by the results of observations and interviews with sources. The results of this study indicate some indications of fraud. First, the seller creates a fake account and colludes with his friend to make a fake offer. Second, the seller who entrusted the goods to the @xxx Instagram account did not send the goods to the auction winner. Third, the seller of the @xxx Instagram account sells goods by mixing genuine and fake products. It is contrary to Islamic law, which prohibits any intentional fraudulent activity. Of the several acts of fraud committed by the perpetrators, they can be subject to Article 28 of the 2016 ITE Law, Article 378 of the Criminal Code, Law no. 20 of 2016 concerning Brands and Geographical Indications, Law Number 11 of 2008 concerning Information and Electronic Transactions, and Article 16 of Law no. 8 of 1999 concerning Consumer Protection.